محاكاة صفة الاتجاهية لليزر الياقوت - جميل طالب, انسام; رمضان عتاب, رسول; خضر جابر, ازهار (University of Thi-Qar Journal of Science, 2009)
This study deals with simulate assumed designs for ruby laser resonator from calculate radius of laser beam at the beam waist, diameter of laser beam and curvature radius of laser beam at distance (z). The results found the best design of ruby laser resonator has very small divergence angle and high degree of directionality. Its found the minimum value of divergence angle was about 0.1033 mrad at R1=40 cm and R2=40 cm.